Comparative transcriptome analysis of hypothalamus-regulated feed intake induced by exogenous visfatin in chicks - Zhuanjian Li; Xuelian Liu; Panpan Zhang; Ruili Han; Guirong Sun; Ruirui Jiang; Yanbin Wang; Xiaojun Liu; Wenya Li; Xiangtao Kang; Yadong Tian (BMC Genomics, 2018)
Abstract Background The intracerebroventricular injection of visfatin increases feed intake. However, little is known about the molecular mechanism in chicks. This study was conducted to assess the effect of visfatin on the feeding behavior of chicks and the associated molecular mechanism. Results In response to the intraventricular injection of 40 ng and 400 ng visfatin, feed intake in chicks was significantly increased, and the concentrations of glucose, insulin, TG, HDL and LDL were significantly altered. Using RNA-seq, we identified DEGs in the chick hypothalamus at 60 min after injection with various doses of visfatin. In total, 325, 85 and 519 DEGs were identified in the treated chick hypothalamus in the LT vs C, HT vs C and LT vs HT comparisons, respectively. The changes in the expression profiles of DEGs, GO functional categories, KEGG pathways, and PPI networks by visfatin-mediated regulation of feed intake were analyzed. The DEGs were grouped into 8 clusters based on their expression patterns via K-mean clustering; there were 14 appetite-related DEGs enriched in the hormone activity GO term. The neuroactive ligand-receptor interaction pathway was the key pathway affected by visfatin. The PPI analysis of DEGs showed that POMC was a hub gene that interacted with the maximum number of nodes and ingestion-related pathways, including POMC, CRH, AgRP, NPY, TRH, VIP, NPYL, CGA and TSHB. Conclusion These common DEGs were enriched in the hormone activity GO term and the neuroactive ligand-receptor interaction pathway. Therefore, visfatin causes hyperphagia via the POMC/CRH and NPY/AgRP signaling pathways. These results provide valuable information about the molecular mechanisms of the regulation of food intake by visfatin.